KEDUDUKAN PERKAWINAN BEDA AGAMA DAN PERKAWINAN CAMPURAN DI INDONESIA - Mariani Mariani (Pascasarjana UIN ANTASARI Banjarmasin, 2020)
There are two categories of mixed marriages in Indonesia, namely mixed marriages between religions / different religions and mixed marriages across countries / different nationalities. This research method using descriptive-analytical method. The conclusions are: Mixed marriages carried out in Indonesia refer to the applicable marriage laws in Indonesia. In order to carry out mixed marriages between Indonesian citizens and citizens of other countries, in general the requirements for marriage as regulated in the marriage law must first be met; Mixed marriages across countries, namely marriages made by Indonesian citizens with foreign citizens are allowed and legalized / recognized by the State, as long as all the terms and conditions regulated by the laws of the respective countries of origin of the bride and groom are fulfilled and there is no prohibition for both of them to carry out wedding; and Islamic Law and Indonesian Positive Law allow marriage between two people of different nationalities, but prohibit mixed marriages due to religious differences and do not obtain legal legality.